Polyamide molding material and its use, as well as moldings produced from said molding material

The polyamide molding compound, comprising a semi-crystalline copolyamide and glass fibers, addresses the issue of surface roughness in glass fiber reinforced injection molded parts, achieving high rigidity, excellent visual properties, and efficient thermal processing.

JP7656408B2Active Publication Date: 2025-04-03EMS PATENT AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020132931
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-09
Filing Date
2020-08-05
Publication Date
2025-04-03
Estimated Expiration
2040-08-05

AI Technical Summary

Technical Problem

Glass fiber reinforced injection molded polyamide products often exhibit dull and rough surfaces due to uneven crystallization and glass fiber effects, which is undesirable for visually exposed parts.

Method used

A polyamide molding compound comprising a semi-crystalline copolyamide formed from specific monomers, combined with 30-70% by weight of at least one filler, such as glass fibers, and optionally 0-8% by weight of additives, to achieve improved surface quality and mechanical properties.

Benefits of technology

The proposed solution results in molded parts with high rigidity, excellent visual properties, and improved thermal processing characteristics, including faster crystallization and reduced cooling time, leading to enhanced manufacturing efficiency and surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656408000001
    Figure 0007656408000001
  • Figure 0007656408000002
    Figure 0007656408000002
  • Figure 0007656408000003
    Figure 0007656408000003
Patent Text Reader

Abstract

To provide polyamide molding compounds that permit the production of moldings that have very good visual properties in addition to a high stiffness.SOLUTION: A polyamide molding compound comprising the following components (A) to (C): (A) 22 to 70 wt.% of a semi-crystalline copolyamide formed from the monomers (a1) to (a5): (a1) 20 to 37.5 mol% 1,6-hexanediamine; (a2) 12.5 to 25 mol% 1,3,4-bis(aminomethyl)cyclohexane; (a3) 0 to 5 mol% a C2-35 diamine, differing from the monomers (a1) and (a2); (a4) 45 to 50 mol% 1,6-hexanedioic acid; and (a5) 0 to 5 mol% a C2-44 dicarboxylic acid; (B) 30 to 70 wt.% of at least one filler; and (C) 0 to 8 wt.% of at least one additive, wherein the component (C) differs from the component (B).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polyamide moulding compounds comprising a semi-crystalline copolyamide, at least one filler and optionally additives. The invention also relates to mouldings produced from these moulding compounds and to the use of the moulding compounds for producing mouldings. [Background technology]

[0002] A number of polyamide molding compounds are known from the prior art, and the composition of the molding compounds is adapted to their desired property profile. In particular for reinforced polyamide molding compounds, in addition to advantageous mechanical properties, a glossy and smooth surface in the moldings produced therefrom should be possible. The technical processing properties of the molding compounds should not be impaired in the process. However, in glass fiber reinforced injection molded products, the surface of the molded part is often dull and rough due to unevenness and glass fiber effects. However, for visible molded parts, which are often relevant for the design of the body, this effect is usually undesirable.

[0003] The surface quality of injection-molded parts is particularly influenced by the crystallization behavior of the copolyamide, where a high temperature of the injection-molding tool can clearly improve the surface quality, but also prolong the cooling time until the demoulding temperature is reached.

[0004] Transparent polyamides are known from GB 1 433 144, from which moldings can be produced at relatively high temperatures without losing good mechanical properties. Here, they are amorphous polyamides formed from mixtures of 1,3-bis(aminomethyl)cyclohexane and aliphatic diamines and mixtures of aromatic and aliphatic dicarboxylic acids. The surface properties of the moldings produced from these molding compounds are not addressed here.

[0005] Fibres consisting of a blend of homopolyamide (PA6 or PA66) and a copolyamide formed from more than 80% by weight of the homopolyamide monomers and less than 20% by weight of 1,3-bis(aminomethyl)cyclohexane and 1,6-hexanediamine are known from GB 2 351 898. As carboxylic acids both aliphatic and aromatic dicarboxylic acids are used. These fibres are particularly suitable for the production of textile materials.

[0006] Polyamide resin compositions are known from EP 1 182 228 A1 and have good production cycles due to the shortened crystallization times. Mouldings produced therefrom show good mechanical properties at temperatures above 100° C. For this purpose, copolyamide resins are used in which the diamine component 1,4-bis(aminomethyl)cyclohexane and the further diamine components p-xylylenediamine or hexamethylenediamine are used and adipic acid is used as the dicarboxylic acid component. The moulding compound further comprises a nucleating agent. Summary of the Invention [Problem to be solved by the invention]

[0007] The object of the present invention is to provide a polyamide molding compound which allows the production of moldings which, in addition to high stiffness, have very good visual properties. [Means for solving the problem]

[0008] This object is achieved by a polyamide moulding compound having the features of claim 1 and by a moulded body having the features of claim 12. The use according to the invention is defined in claim 14.

[0009] According to the present invention, there is provided a polyamide molding compound comprising or consisting of the following components (A) to (C): (A) 22 to 70% by weight of a semicrystalline copolyamide formed from monomers (a1) to (a5): (a1) 20 to 37.5 mol% of 1,6-hexanediamine; (a2) 1,3,4-bis(aminomethyl)cyclohexane 12.5 to 25 mol%; (a3) 0-5 mol % of at least one diamine having 2 to 35 carbon atoms, different from the monomers (a1) and (a2); (a4) 1,6-hexanedioic acid 45 to 50 mol% (a5) 0-5 mol % of at least one dicarboxylic acid having 2 to 44 carbon atoms, different from monomer (a4); wherein the proportions of monomers (a1), (a2) and (a3) ​​add up to 50 mol% based on the total amount of diamines used; and wherein the proportion of monomers (a4) and (a5) totals 50 mol-%, based on the sum of the dicarboxylic acids used; and Here, the proportions of the monomers (a1) to (a5) are 100 mol % in total. (B) 30 to 70% by weight of at least one filler; and (C) 0 to 8% by weight of at least one additive; Here, component (C) is different from component (B), and the proportions of components (A) to (C) are 100% by weight in total.

[0010] Definition of Terms Notations and abbreviations of polyamides and their monomers In the sense of the present invention, the term "polyamide" (abbreviation PA) is understood as a generic term; it includes homopolyamides and copolyamides. The notations and abbreviations selected for the polyamides and their monomers correspond to those set out in ISO standard 16396-1 (2015, (D)). The abbreviations used here are used below as synonyms of the IUPAC names of the monomers. In particular, the following abbreviations are used for the monomers in this application: 1,3-BAC stands for 1,3-bis(aminomethyl)cyclohexane (also called 1,3-cyclohexanedimethanamine, CAS number 2579-20-6); 1,4-BAC stands for 1,4-bis(aminomethyl)cyclohexane (also called 1,4-cyclohexanedimethanamine, CAS number 2549-93-1); IDP stands for isophronediamine (3-(aminomethyl)-3,5,5-trimethylcyclohexanamine, 1-amino-3-aminomethyl-3,5,5-trimethylcyclohexane or cyclohexanemethanamine, 5-amino-1, ... methyl, CAS number 2855-13-2); MACM, bis(4-amino-3-methylcyclohexyl)methane, also known as 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, CAS number 6864-37-5); PACM, bis(4-amino-cyclohexyl)methane, also known as 4,4'-diamino-cyclohexylmethane, CAS number 1761-71-3); 6, 1,6-hexanediamine, CAS number 124-09-4; T, terephthalic acid, CAS number 100-21-0; I, isophthalic acid, CAS number 121-95-5; 6, 1,6-hexanedioic acid, CAS number 124-04-9.

[0011] General information on compounds The terms "containing" and "comprising" in the claims and the specification mean that further components are not excluded. Within the framework of the present invention, the term "consist of" is to be understood as a preferred embodiment of the terms "containing" or "comprising". When a group is defined as "containing" or "comprising" at least a certain number of components, this is also to be understood as preferably disclosing a group that "consists of" these components.

[0012] General discussion on quantity indication The polyamide molding compound according to the invention comprises or consists of components (A), (B) and optionally (C), with the provision that the sum of components (A), (B) and (C) is 100% by weight. The ranges of the amounts of components (A), (B) and (C) are given in order to be understood as meaning that any amount for each of the components can be selected within the given ranges, provided that the strict provision that the sum of all components (A) to (C) is 100% by weight is met.

[0013] Semi-crystalline polyamide In the sense of the present invention, semicrystalline copolyamides are copolyamides which preferably have a melting point and / or a heat of fusion in differential scanning calorimetry (DSC) according to ISO 11357-3 (2013) of more than 4 J / g at a heating rate of 20 K / min.

[0014] Polyamide Molding Compound The polyamide molding compound according to the invention contains or consists of components (A) and (B) and optionally (C).

[0015] The proportion of component (A) in the polyamide molding compound is preferably within the range of 29 to 64.9% by weight, particularly preferably within the range of 36 to 59.8% by weight, relative to the total weight of the polyamide molding compound.

[0016] The proportion of component (B) in the polyamide molding compound is preferably in the range of 35 to 65% by weight, particularly preferably in the range of 40 to 60% by weight, relative to the total weight of the polyamide molding compound.

[0017] The proportion of component (C) in the molding compound is preferably in the range of 0.1 to 6% by weight, particularly preferably in the range of 0.2 to 4% by weight, relative to the total weight of the polyamide molding compound.

[0018] The behavior of polyamide molding compounds in thermoplastic processing by injection molding or extrusion into molded parts is influenced by a range of thermal properties of the molding compound.

[0019] Cycle time has a significant impact on the economics of the injection molding process. The cooling time of the molding compound in the tool is limited until the molded part is stable enough to be demolded without deformation or ejector marks. Ideally, the molding compound should also be completely crystallized within the cooling time in the tool. Delay in crystallization after demolding leads to shrinkage and deformation. Fast crystallizing molding compounds are characterized by fast crystallization rates and short cycle times.

[0020] A lower melting point allows for lower mass temperatures, thus saving energy, while at the same time preventing the associated thermal degradation and discoloration of the molding compound.

[0021] At the same time, however, the temperature and rate of crystallization do not have to be so high that the molding compound solidifies immediately upon contact with the surface of the cold tool. An effective holding pressure without premature solidification of the molding compound is necessary for accurate release of the surface. The molding compound according to the invention achieves a very good surface with good crystallinity within the minimum cooling time dictated by the thermal conductivity of polyamide molding compounds with normal wall thicknesses.

[0022] At the very least, a molded article having high rigidity, which is represented by a high elastic modulus, is desired.

[0023] For a high gloss surface, the tool temperature should usually be higher than the glass transition temperature, but if the tool temperature is too high, the cooling time will be unnecessarily long and may cause sticking or removal marks on the molded part surface.

[0024] It must also be noted that in the case of tool temperatures of 190-200 °C, water must be replaced by heat transfer oil as a heat carrier. In that case, additional expensive construction measures are required. Both the additional costs for tool temperature control and the long cycle times are disadvantageous for the molding compound, since they increase the cost of the parts produced from it.

[0025] The polyamide molding compound according to the present invention preferably has a glass transition temperature in the range of 50 to 200°C, particularly preferably in the range of 60 to 190°C, and more particularly preferably in the range of 65 to 90°C.

[0026] The polyamide molding compound according to the present invention preferably has a melting point in the range of 100 to 260°C, particularly preferably in the range of 205 to 245°C, and more particularly preferably in the range of 210 to 235°C.

[0027] The polyamide molding compound according to the present invention preferably has a crystallization temperature within the range of 130 to 200°C, more preferably within the range of 140 to 200°C.

[0028] The polyamide molding compound according to the invention preferably has a crystallization rate in the range of 12 to 50 J / g min, particularly preferably in the range of 15 to 47 J / g min, and more particularly preferably in the range of 23 to 45 J / g min.

[0029] The moulded bodies produced from the polyamide moulding compound preferably have a modulus of elasticity, determined in accordance with ISO 527, of at least 5000 MPa, preferably at least 8000 MPa, particularly preferably at least 12000 MPa.

[0030] The moulded bodies produced from the polyamide moulding compound preferably have a gloss value, measured in the dry state at 60°, of 70 to 100 GU according to DIN EN 2813 (2015).

[0031] Moulded bodies produced from the polyamide moulding compound preferably have a gloss value, measured in the conditioned state at 60°, of 60 to 100 GU according to DIN EN 2813 (2015).

[0032] The polyamide molding compound according to the invention or the moldings produced therefrom can preferably have one or more, particularly preferably all, of the properties named above (glass transition temperature, melting point, crystallization temperature, crystallization rate, elastic modulus and gloss value).

[0033] Component (A) The proportion of monomer (a1) in the semicrystalline copolyamide (component (A)) is preferably in the range of 20 to 35 mol%, particularly preferably in the range of 22.5 to 32.5 mol%, more particularly preferably in the range of 25 to 32.5 mol%. The proportion of monomer (a2) in the semicrystalline copolyamide is preferably in the range of 15 to 25 mol%, particularly preferably in the range of 17.5 to 22.5 mol%. The proportion of monomer (a3) ​​in the semicrystalline copolyamide is preferably in the range of 0 to 2.5 mol%. The proportions of monomers (a1), (a2) and (a3) ​​total 50 mol% based on the total of the diamines used.

[0034] The proportion of monomer (a4) in the semicrystalline copolyamide is preferably within the range of 47.5 to 50 mol %. The proportion of monomer (a5) in the semicrystalline copolyamide is preferably within the range of 0 to 2.5 mol %. The proportions of monomers (a1), (a4) and (a5) are 50 mol % in total based on the total of the dicarboxylic acids used.

[0035] The at least one monomer (a3) ​​is preferably selected from the group consisting of ethylenediamine, butanediamine, pentanediamine, methylpentanediamine, 1,8-octanediamine, methyloctanediamine, 1,9,nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, trimethylhexamethylenediamine, 1,4-cyclohexanediamine, bis-(4-amino-3-methyl-cyclohexyl)methane, bis-(4-amino-cyclohexyl)methane, isophoronediamine, 1,4-bis(aminomethyl)cyclohexane, m-xylylenediamine, p-xylylenediamine bis(aminocyclohexyl)propane and its alkyl derivatives, norbornanediamines and bis(aminomethyl)norbornane.

[0036] A further preferred group from which the at least one monomer (a3) ​​is selected consists of pentanediamine, methylpentanediamine, methyloctanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, trimethylhexamethylenediamine, bis-(4-amino-3-methyl-cyclohexyl)methane, bis-(4-amino-cyclohexyl)methane, isophoronediamine, 1,4-bis(aminomethyl)cyclohexane, m-xylylenediamine and p-xylylenediamine.

[0037] It is particularly preferred that the at least one monomer (a3) ​​is selected from the group consisting of pentanediamine, methylpentanediamine, methyloctanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, trimethylhexamethylenediamine, bis-(4-amino-3-methyl-cyclohexyl)methane, bis-(4-amino-cyclohexyl)methane and isophoronediamine.

[0038] As monomer (a3) ​​it is particularly preferable to use bis-(4-amino-3-methyl-cyclohexyl)methane, bis-(4-amino-cyclohexyl)methane and / or isophoronediamine.

[0039] The at least one monomer (a5) may be selected from the group consisting of isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, 1,9-nonanedioic acid, 1,10-decanedioic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,13-tridecanedioic acid, 1,14-tetradecanedioic acid, 1,15-pentadecanedioic acid, 1,16-hexadecanedioic acid, 1,17-heptadecanedioic acid, 1,18-octadecanedioic acid, arachidic acid, nitric acid, behenic acid, cyclohexanedioic acid, It is preferably selected from the group consisting of phenylindanedicarboxylic acid, phenylenediooxydiacetic acid and dimeric fatty acids having 35 or 44 carbon atoms.

[0040] A further preferred group from which the at least one monomer (a5) is selected consists of isophthalic acid, terephthalic acid, 1,10-decanedioic acid, 1,12-dodecanedioic acid, 1,14-tetradecanedioic acid, 1,16-hexadecanedioic acid.

[0041] It is particularly preferred that the at least one monomer (a5) is selected from the group consisting of isophthalic acid, terephthalic acid, 1,10-decanedioic acid and 1,12-dodecanedioic acid.

[0042] As monomer (a5), it is particularly preferable to use isophthalic acid and / or terephthalic acid.

[0043] The semi-crystalline copolyamide (component (A)) preferably contains neither lactams nor amino acids.

[0044] Ingredient (B) The term filler (ingredient (B)) includes fibrous or acicular fillers, particulate fillers, and mixtures thereof.

[0045] The fillers can preferably be coated or surface treated, i.e. they can be provided with a suitable finishing or binder system or can be otherwise surface activated. Systems based on urethanes, silanes, epoxides, polyamides, polyhydroxyethers, acrylates, their respective combinations or mixtures thereof can be used for this purpose, for example. The leveling or binder system can also contain other auxiliaries such as antistatic agents or mold lubricants (mold release agents).

[0046] The fibrous or acicular fillers are preferably selected from the group consisting of glass fibers, carbon fibers, basalt fibers, slag fibers, metal fibers, whiskers, mineral fibers, wollastonite, ground glass fibers, ground carbon fibers, ground mineral fibers and mixtures thereof. The fibrous or acicular fillers are particularly preferably selected from the group consisting of glass fibers, carbon fibers, basalt fibers and mixtures thereof. It is more particularly preferred to use only glass fibers as the fibrous or acicular fillers.

[0047] The glass or carbon fibers can be used as stable fibers (staple fibers) or continuous fibers (rovings).

[0048] The glass or carbon fibers may have a round, oval, elliptical, angular or rectangular cross section. Fibers with non-circular cross sections ("flat fibers") may also be used, in particular fibers with an oval, elliptical, angular or rectangular cross section.

[0049] The appearance of the glass fibers can be stretched or spiral.

[0050] Glass fibres from all glass types such as A-, C-, D-, E-, E-CR-, L-, LD-, M-, NE-, S-, R-, Ar-glass or any desired mixtures thereof can be used. Glass fibres from E-glass or mixtures with E-glass fibres or mixtures with E-glass fibres are preferred.

[0051] The fiber length of the short glass fibers (staple glass fibers) is preferably 1 to 25 mm, more preferably 1.5 to 20 mm, particularly preferably 2 to 12 mm, and even more particularly preferably 2 to 8 mm.

[0052] The diameter of the glass fiber is preferably 5 to 20 μm, more preferably 5 to 15 μm, and particularly preferably 6 to 12 μm.

[0053] When the glass fibers are used as continuous fibers (rovings) in the pultrusion process, the diameter is preferably 20 μm or less, more preferably 18 μm or less, and particularly preferably 10 to 17 μm.

[0054] The diameter of the carbon fibers is preferably from 3 to 12 μm, more preferably from 4 to 10 μm, and particularly preferably from 4 to 9 μm.

[0055] In the case of flat fibers, the aspect ratio, ie the ratio of the main cross-sectional axis to the secondary cross-sectional axis, is 1.5-8, preferably 2-6, and particularly preferably 3-5.

[0056] Of the flat fibers, flat glass fibers are particularly preferred.

[0057] The length of the cross-sectional axis of the flat glass fiber is 3 to 40 μm, the length of the minor cross-sectional axis is preferably 3 to 20 μm, particularly preferably 4 to 10 μm, and the length of the main cross-sectional axis is 6 to 40 μm, particularly preferably 12 to 30 μm.

[0058] The particulate filler is preferably selected from the group consisting of dolomite, silicates, quartz, talc, mica, kaolin, perlite, silica, precipitated or pyrogenic silicon dioxide, diatomaceous earth, titanium dioxide, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, ground or precipitated calcium carbonate, chalk, calcium, limestone dust, slate powder, feldspar, barium carbonate, barium sulfate, synthetic sheet silicate, natural sheet silicate, permanently magnetic or magnetizable metals or alloys, glass flakes, glass spheres, hollow glass spheres, hollow spherical silicate fillers, and mixtures thereof. Particularly preferably, the particulate filler is selected from the group consisting of silicates, quartz, talc, mica, kaolin, perlite, silica, precipitated or pyrogenic silicon dioxide, diatomaceous earth, titanium dioxide, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, ground or precipitated calcium carbonate, chalk, calcium, limestone dust, slate powder, feldspar, barium carbonate, barium sulfate, synthetic silicate sheets, natural silicate sheets, glass flakes, glass spheres, hollow glass spheres, hollow spherical silicate fillers, and mixtures thereof. Particulate fillers are more particularly preferably selected from the group consisting of silicates, talc, mica, kaolin, titanium dioxide, ground or precipitated calcium carbonate, chalk, limestone dust, slate powder, synthetic silicate sheets, natural silicate sheets, glass flakes, glass spheres, hollow glass spheres, and mixtures thereof.

[0059] As filler (component (B)) in the polyamide molding compound according to the invention, it is preferable to use at least one fibrous or acicular filler or a mixture of at least one fibrous or acicular filler and at least one particulate filler.

[0060] When a mixture of at least one fibrous or acicular filler and at least one particulate filler is used, the proportion of the particulate filler accounts for no more than half (maximum half) of the total amount of filler, preferably no more than one third, particularly preferably no more than one quarter.

[0061] It is particularly preferable to use exclusively fibrous or acicular fillers as fillers in the polyamide moulding compounds according to the invention.

[0062] Ingredients (C) According to a preferred embodiment of the present invention, the at least one additive (component (C)) is selected from the group consisting of inorganic and organic stabilizers, in particular antioxidants, antiozonants, light stabilizers, in particular UV stabilizers, UV absorbers or UV blockers, mold lubricants, dyes, marking agents, pigments, black carbon, graphite, graphene, polyamide oligomers, carbon nanotubes, photochromic agents, antistatic agents, mold release means, antiblocking agents, chain extension additives, chain shortening additives, optical brighteners, IR absorbers, NIR absorbers, non-halogen flame retardants, metal pigments, metal flakes, metal coated particles, and mixtures thereof.

[0063] The number-average molar mass of the polyamide oligomer is preferably 1000 to 6000 g / mol, particularly preferably 2500 to 4500 g / mol, determined by gel permeation chromatography (GPC) with triple detector.

[0064] The at least one additive can also be added in the form of a masterbatch. As the base polymer of the masterbatch, it is preferred to use a polyamide. This polyamide is preferably selected from the group consisting of PA6, PA66, PA12, PA1012, PA1212, PA6 / 12, PA6 / 66, PA6 / 69 and mixtures thereof, or it consists of the copolyamide (A) itself.

[0065] Molded body The invention likewise provides moldings which can be produced from the above-mentioned molding compounds. The moldings according to the invention can be produced from the polyamide molding compounds according to the invention by conventional processing techniques, such as injection molding.

[0066] A preferred embodiment provides that the moulding is selected from the group consisting of non-lacquered visible parts with or without a function, in the passenger compartment or trunk of a motor vehicle, in the home, in mechanical engineering, in electrical devices, electronic devices, household appliances, furniture, in particular fan blades, gear sticks, rocker switches, buttons, rotary controls, straps, operating elements for seat adjustment, operating elements on steering columns, operating levers, operating elements, drawers, holders for accessories, drink holders, luggage hooks, covers, light switches, razor heads, scissor parts, threaded rods, in particular insulin pumps, housings and decorative elements.

[0067] use The invention further relates to the use of the above-mentioned polyamide moulding compounds according to the invention for producing functional or non-functional, unlacquered visible parts in the passenger compartment or trunk of a motor vehicle, in the household, in mechanical engineering, for electrical equipment, electronic devices, household appliances, furniture, in particular fan blades, gear sticks, rocker switches, buttons, rotary controls, straps, operating elements for seat adjustment, operating elements on steering columns, operating levers, operating elements, drawers, holders for accessories, drink holders, luggage hooks, covers, light switches, razor heads, scissor parts, threaded rods, in particular insulin pumps, housings, decorative elements.

[0068] The subject matter according to the invention will be explained in more detail with reference to the following examples, without being limited to the particular embodiments shown herein.

[0069] Examples and Comparative Examples Measurement method

[0070] Relative Viscosity The relative viscosity was measured at 20°C according to IS 307 (2007). For this purpose, 0.5 g of polymer pellets were weighed into 100 ml of m-cresol; calculation of relative viscosity (RV) according to RV=t / t0 was done based on section 11 of the standard.

[0071] Glass transition temperature (Tg), heat of crystallization, heat of fusion, and melting point Measurements were performed on pellets according to SO11357-3(2013). Differential scanning calorimetry (DSC) was performed at each of the three heating steps with a heating rate of 20 K / min. Cooling was performed at 20 K / min after the first heat. The samples were quenched in dry ice after the second heat. The glass transition temperature (Tg) was measured at the third heat and the melting point at the second heat. The crystallization temperature and crystallization rate were measured on cooling after the first heat. The peak maximum temperature is defined as the melting point. The center of the glass transition range, defined herein as the glass transition temperature (Tg), was measured using the "half height" method.

[0072] Gloss value at 60° The gloss values ​​at a measuring angle of 60° were measured according to DIN EN ISO 2813 (2015) at 23° C. with a plate of dimensions 60×60×2 mm using a glossmeter (ATP Messtechnik GmbH, Germany) and are reported in gloss units (GU).

[0073] Elasticity The elastic modulus was measured according to ISO 527 (2012) at 23 °C and a tensile speed of 1 mm / min using ISO tensile rods (type A1, mass 170 × 20 / 10 × 4) manufactured according to the standard: ISO / CD 3167 (2003).

[0074] Molar mass measurement Molar mass measurements were performed using gel permeation chromatography (GPC) equipped with a triple detector for refractive index, viscosity and light scattering (7° and 90°). Samples are dissolved in hexafluoroisopropanol (HFIP) (approximately 5 mg of polymer in 1 ml) for measurement and filtered through disposable syringe filters before loading into vials. Unit: Malvern OMNISEC GPC system Software:Malvern OMNISEC version 10.41 Column: Malvern HFIP3000+HFIP6000M 300×7.8mm, particle size 10μm Eluent: HFIP containing 0.1M potassium trifluoroacetate Column temperature: 40℃ Detector temperature: 40℃ Flow rate 1.0ml / min

[0075] Molecular weights (number average Mn and weight average Mw) are determined using the triple detection method. Calibration of the GPC system is performed using monodisperse PMMA standards. Three measurements are each performed. The arithmetic mean of the molecular weights is shown.

[0076] The solvent HFIP was obtained in HPLC quality from Fluorochem, Germany, and potassium trifluoroacetate was obtained from Sigma-Aldrich, Switzerland.

[0077] Disposable filters are available from Chemie Brunschwig, Switzerland under the designation SFPTFE0250022NBC (PTFE membrane, pore size 0.45 μm, filter diameter 25 mm). Disposal filters are available from VWR International GmbH, Germany.

[0078] Preparation of test specimens Test specimens were prepared using pellets with a moisture content of less than 0.1% by weight.

[0079] The test specimens were produced on an Arburg injection molding machine, model Allrounder 420 C 1000-250. The process used an increasing and decreasing cylinder temperature from the feed to the nozzle.

[0080] ISO Tensile Rod Cylinder temperature: 260 / 265 / 270 / 275 / 280 / 275℃ Tool temperature: 110℃

[0081] Plate 60×60×2mm Cylinder temperature: 270 / 275 / 280 / 285 / 290 / 285℃ Tool temperature: 110℃

[0082] Abrasive tools were used to prepare the plates.

[0083] Unless otherwise stated, the test specimens were used in dry condition: for this purpose, they were stored in a dry environment, i.e. on silica gel, at room temperature for at least 48 hours after injection molding.

[0084] Plates of 60 x 60 x 2 mm for surface gloss measurements in the conditioned state were stored at 70°C and 62% relative humidity according to ISO 1110 for 7 days.

[0085] Starting materials Tables 1 to 3 show the materials used in the examples and comparative examples.

[0086] [Table 1-1]

[0087] [Table 1-2]

[0088] [Table 1-3]

[0089] [Table 1-4]

[0090] [Table 2]

[0091] [Table 3]

[0092] General rules for the production of copolyamides (A) The preparation of the copolyamide according to the invention is carried out in a manner known per se in known stirred pressure autoclaves having a presentation vessel and a reaction vessel.

[0093] Deionized water is presented in the presentation vessel, monomers and possible additives are added. Inertization is carried out several times with nitrogen gas. Heating is performed to 180-230 ° C, with stirring at the pressure adopted to obtain a homogeneous solution. The solution is pumped through a screen into the reaction vessel and heated to the desired reaction temperature of 250-300 ° C, at a pressure of up to 30 bar. The preparation is maintained at the reaction temperature for 2-4 hours in the pressure phase. In the following expansion phase, the pressure can be reduced to atmospheric pressure within 1-2 hours and the temperature reduced slightly. In the following degassing phase, the preparation is maintained at a temperature of 250-300 ° C and atmospheric pressure for 0.5-6 hours. The molten polymer is discharged in the form of strands, cooled to 10-80 ° C in a water bath and pelletized. The pellets are dried at 60-120 ° C under nitrogen or in vacuum to a moisture content of less than 0.1% by weight.

[0094] Suitable catalysts for accelerating the polycondensation reaction are phosphorus-containing acids, their salts or organic derivatives, such as H3PO2, H3PO3, H3PO4, etc. The catalyst is mixed in an amount of preferably 0.01 to 0.5% by weight, particularly preferably 0.03 to 0.1% by weight, based on the polyamide.

[0095] Suitable antifoaming agents to avoid foam formation during degassing include silicones or silicone derivatives and are preferably aqueous 10% emulsions used in an amount of 0.01 to 1.0% by weight, particularly preferably 0.01 to 0.10% by weight, based on the polyamide.

[0096] The relative viscosity and therefore the molar mass can be set in a manner known per se, for example via monofunctional amines or carboxylic acids and / or difunctional diamines or dicarboxylic acids as chain regulators.Typical amounts of monofunctional chain regulators used are 10 to 200 mmol per kg of copolyamide.

[0097] General rules for the manufacture of the polyamide molding compounds according to the invention To produce the polyamide molding compounds according to the invention, components (A), (B) and, optionally, (C) are mixed in a conventional compounder, such as a single- or twin-screw extruder or a screw kneader, where the components are either metered individually via gravimetric or volumetric trays into the feed or into a side feeder, respectively, or are fed in the form of a dry blend.

[0098] If additives (component (C)) are used, they can be introduced directly or in the form of a masterbatch. The carrier material of the masterbatch is preferably a polyamide or a polyolefin. Among the polyamides, copolyamides (A) are particularly suitable for this.

[0099] Dry pellets of component (A) and, optionally, additive (C) are mixed in a closed container to prepare a dry blend. The mixture is homogenized for 10 to 40 minutes using a wobble mixer, tumble mixer or tumble dryer. Homogenization can be carried out under dry protective gas to avoid moisture absorption.

[0100] Compounding is carried out with a cylinder temperature set at 250-310°C, the temperature of the first cylinder can be set below 90°C. Degassing can be done before the nozzle. This can be done by vacuum or air. The melt is discharged in strands and cooled to 10-80°C in a water bath before pelletizing. Alternatively, the melt can be forced into a water bath through a perforated plate with a cutting device, and the cut pellets can be separated in a post-processing path (underwater pelletizing). The pellets are dried at 60-120°C under nitrogen or in vacuum to a moisture content of less than 0.1% by weight.

[0101] Production of polyamide molding compound according to Example 3 Dry pellets of copolyamide PA66 / 1.3-BAC6 (A) and additive (CM1) were mixed to form a dry blend, in effect in the ratios shown in Example 3 of Table 4. The mixture was homogenized using a tumble mixer for approximately 20 minutes.

[0102] The polyamide molding compounds were produced in a twin-screw extruder of the Werner & Pfleiderer type ZSK25, where the dry blend was metered into the feed via a metering scale. The glass fibers (B1) were conveyed into the melt before the nozzle by a metering scale and a side feeder 6 housing zones.

[0103] The temperature of the first housing was set at 50°C; the temperature of the remaining housings was set at 260-280°C. The speed was 250 rpm and the throughput was 15 kg / h. No degassing was performed. The molten strand was cooled in a water bath, cut and the resulting pellets were dried in vacuum (30 mbar) at 100°C for 24 hours to a moisture content of less than 0.1% by weight.

[0104] Experimental Results The molding compounds according to the invention were investigated with respect to surface gloss and modulus of elasticity, and the results of these tests are shown in Tables 4 and 5.

[0105] Moulding compounds not according to the invention were equally tested for surface gloss and modulus under the same measurement conditions. The results of the comparative examples are summarised in Table 6.

[0106] [Table 4]

[0107] [Table 5]

[0108] [Table 6]

[0109] Discussion of results The plates of the polyamide moulding compounds according to the invention of Examples 1-8 and 11-17 filled with glass fibres consistently show better gloss values ​​than the comparative plates of the polyamide moulding compounds of Comparative Examples 18-21, in both the dry and conditioned state.

[0110] Plates from the polyamide molding compounds of Examples 9 and 10, filled only with mineral or only with a mixture of glass fibre and mineral, show the best results.

[0111] The plate from comparative example 21 PA66 filled with glass fibres shows an insufficient surface quality and is therefore not suitable for visible parts.

[0112] The DSC measurement of the glass fiber filled PA1,3-BAC6 of Comparative Example 20 after the first heating no longer shows any crystallization. Therefore, the content of 1,3-bis(aminomethyl)cyclohexane at 50 mol% is too high. This also affects the gloss value, which is significantly reduced by conditioning, since post-crystallization occurs in this process.

[0113] In order to be able to achieve a modulus of elasticity of at least 5000 MPa, the polyamide moulding compounds according to the invention must contain a filler, as can be seen from the polyamide moulding compound of Comparative Example 22.

Claims

1. A polyamide molding material comprising or consisting of the following components (A) to (C): (A) 22 to 70% by weight of a semicrystalline copolyamide formed from monomers (a1) to (a5): (a1) 20 to 37.5 mol% of 1,6-hexanediamine; (a2) 1,3-bis(aminomethyl)cyclohexane 12.5 to 25 mol%; (a3) 0 to 5 mol % of at least one diamine having 2 to 35 carbon atoms, different from the monomers (a1) and (a2); (a4) 45 to 50 mol % of 1,6-hexanedioic acid; and (a5) 0 to 5 mol % of at least one dicarboxylic acid having 2 to 44 carbon atoms, different from the monomers (a4); provided that the proportions of monomers (a1), (a2) and (a3) ​​correspond to the sum of the diamines used, totalling 50 mol %; and the proportion of monomers (a4) and (a5) corresponds to the sum of the dicarboxylic acids used, totalling 50 mol %; and The proportions of the monomers (a1) to (a5) total 100%; (B) 30 to 70 weight percent of at least one filler; and (C) 0 to 8% by weight of at least one additive; However, component (C) differs from component (B) in that the total proportions of components (A) to (C) is 100% by weight.

2. the proportion of component (A) in the polyamide molding material is in the range from 29 to 64.9% by weight, based on the total weight of the polyamide molding material; and / or the proportion of component (B) in the polyamide molding material is in the range from 35 to 65% by weight, based on the total weight of the polyamide molding material; and / or The proportion of component (C) in the polyamide molding material is within the range of 0.1 to 6% by weight, based on the total weight of the polyamide molding material; 2. The polyamide molding material according to claim 1 .

3. the proportion of monomer (a1) in said semicrystalline copolyamide is in the range from 20 to 35 mol %; and / or the proportion of monomers (a2) in the copolyamide is in the range from 15 to 25 mol %; the proportion of monomer (a3) ​​in the copolyamide is in the range from 0 to 2.5 mol %, provided that the proportions of the monomers (a1), (a2) and (a3) ​​correspond to the sum of the diamines used, and total 50 mol %.

3. The polyamide molding material according to claim 1 or 2.

4. the proportion of monomers (a4) in the copolyamide is in the range from 47.5 to 50 mol %; and / or the proportion of monomer (a5) in the copolyamide is in the range from 0 to 2.5 mol %, provided that the proportions of monomers (a4) and (a5) correspond to the sum of the dicarboxylic acids used, totalling 50 mol %; 4. The polyamide molding material according to claim 1 ,

5. at least one monomer (a3) ​​is selected from the group consisting of ethylenediamine, butanediamine, pentanediamine, methylpentanediamine, 1,8-octanediamine, methyloctanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, trimethylhexamethylenediamine, 1,4-cyclohexanediamine, 1,3-cyclohexanediamine, bis-(4-amino-3-methyl-cyclohexyl)methane, bis-(4-amino-cyclohexyl)methane, isophoronediamine, 1,4-bis(aminomethyl)cyclohexane, m-xylylenediamine, p-xylylenediamine bis(aminocyclohexyl)propane and its alkyl derivatives, norbornanediamines and bis(aminomethyl)norbornane; and / or at least one monomer (a5) is selected from the group consisting of isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, 1,9-nonanedioic acid, 1,10-decanedioic acid, 1,11-undecanedioic acid, 1,12-dodecanedioic acid, 1,13-tridecanedioic acid, 1,14-tetradecanedioic acid, 1,15-pentadecanedioic acid, 1,16-hexadecanedioic acid, 1,17-heptadecanedioic acid, 1,18-octadecanedioic acid, arachidic acid, Nippon acid, behenic acid, cyclohexanedioic acid, phenylindanedicarboxylic acid, phenylenedioxydiacetic acid, and dimeric fatty acids having 35 or 44 carbon atoms; 5. The polyamide molding material according to claim 1 ,

6. At least one filler (B) is selected from the group consisting of fibrous or acicular fillers, particulate fillers, and mixtures thereof, which are optionally coated or surface treated; 6. The polyamide molding material according to claim 1 ,

7. the fibrous or acicular filler is selected from the group consisting of glass fibers, carbon fibers, basalt fibers, slag fibers, metal fibers, whiskers, mineral fibers, wollastonite, ground glass fibers, ground carbon fibers, ground mineral fibers and mixtures thereof; 7. The polyamide molding material according to claim 6.

8. the particulate filler is selected from the group consisting of dolomite, silicates, quartz, talc, mica, kaolin, perlite, silica, precipitated or calcined silicon dioxide, diatomaceous earth, titanium dioxide, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, ground or precipitated calcium carbonate, chalk, calcium, limestone dust, slate powder, feldspar, barium carbonate, barium sulfate, synthetic silicate sheets, natural silicate sheets, permanently magnetic or magnetizable metals or alloys, glass flakes, glass spheres, hollow glass spheres, hollow spherical silicate fillers, and mixtures thereof; 7. The polyamide molding material according to claim 6.

9. the at least one additive is selected from the group consisting of inorganic and organic stabilizers, antioxidants, antiozonants, light stabilizers, UV stabilizers, UV absorbers or UV blockers, mold lubricants, dyes, marking agents, pigments, black carbon, graphite, graphene, polyamide oligomers, carbon nanotubes, photochromic agents, antistatic agents, mold release agents, antiblocking agents, chain extension additives, chain shortening additives, optical brighteners, IR absorbers, NIR absorbers, non-halogen flame retardants, metal pigments, metal flakes, metal coated particles and mixtures thereof; 9. The polyamide molding material according to claim 1 ,

10. The polyamide molding compound according to any one of claims 1 to 9, characterized in that it has at least one of the following properties: a glass transition temperature in the range of 50 to 200°C; and / or - melting point in the range of 100-260°C; and / or the crystallization temperature is in the range of 60 to 190°C; and / or The crystallization rate is in the range of 13 to 50 J / g min.

11. The polyamide molding material according to any one of claims 1 to 10, characterized in that the moldings produced from the polyamide molding material have at least one of the following properties: the mouldings produced from the polyamide moulding material have an elastic modulus, measured according to ISO 527, of at least 5000 MPa; and / or A gloss value at 60° dry, measured according to DIN EN 2813 (2015), of 70 to 100 GU; and / or The gloss value at 60° conditioning, measured according to DIN EN 2813 (2015), is 60 to 100 GU.

12. A molding produced from the polyamide molding material according to any one of claims 1 to 11.

13. the mouldings are selected from the group consisting of functional or non-functional non-lacquered visible parts for the passenger compartment or trunk of a motor vehicle, for household use, for mechanical engineering, for electrical equipment, for electronic devices, for household appliances, for furniture, for fan blades, gear sticks, rocker switches, buttons, rotary control devices, straps, actuating elements for seat adjustment, actuating elements on steering columns, actuating levers, actuating elements, drawers, holders for accessories, drink holders, luggage hooks, covers, light switches, razor heads, scissor parts, threaded rods, insulin pumps, housings, decorative elements, The molded article according to claim 12 .

14. Use of the polyamide molding material according to any one of claims 1 to 10 for producing functional or non-functional, unlacquered, visible parts in the passenger compartment or trunk of a motor vehicle, in the home, in mechanical engineering, for electrical equipment, electronic devices, household appliances, furniture, fan blades, gear sticks, rocker switches, buttons, rotary controls, straps, operating elements for seat adjustment, operating elements on steering columns, operating levers, operating elements, drawers, holders for accessories, drink holders, luggage hooks, covers, light switches, razor heads, scissor parts, threaded rods, insulin pumps, housings and decorative elements.

Citation Information

Patent Citations

  • JP1974055796A

  • Polyamide resin composition

    JP2001115017A

  • Glass filler-reinforced polyamide molding compounds based on amorphous copolyamides

    JP2018062651A

  • Polyamide molding material and molded article thereof

    JP2018178117A